A prospective, randomized and controlled study of interscalene brachial plexus block for arthroscopic shoulder surgery: A comparison of C5 and conventional approach, a CONSORT-compliant article. Issue 37 (September 2016) - Shin, Hyun-Jung; Na, Hyo-Seok; Oh, Ah-Young; Hwang, Jung-Won; Kim, Byung-Gun; Park, Hee-Pyoung; Jeon, Young-Tae; Min, Seong-Won; Ryu, Jung-Hee
Abstract: Background: The shoulder area is mainly innervated with the C5 and C6 nerve roots, and interscalene brachial plexus block (ISB) is widely used for postoperative analgesia after shoulder surgery. However, it is associated with adverse effects, such as numbness and weakness in the blocked arm due to an unwanted block of the lower brachial plexus (C7-T1). We hypothesized that the C5 approach during ISB would provide postoperative analgesia while minimizing adverse events after arthroscopic shoulder surgery. Methods: A total of 92 patients scheduled for arthroscopic shoulder surgery were enrolled and randomly assigned to 1 of the 3 groups: The control (no ISB, n = 31), conventional ISB (ISB with the conventional approach, n = 31), or C5 ISB (ISB with the C5 approach, n = 30) group. ISB was performed before the induction of anesthesia, and a subacromial catheter was placed in all patients at the end of the surgery. Postoperative pain scores, numbness, and weakness were recorded at 2, 8, and 24 hours after surgery. Oxygen saturation and overall patient satisfaction scores were also assessed at 1 and 48 hour after surgery, respectively. Results: The pain scores were lower in the conventional ISB group and the C5 ISB group than in the control group at postoperative 2 and 8 hours ( P  < 0.05). The incidence and degree of numbness and weakness of the blocked arm were significantly lower in the C5 ISB group than in the conventional ISB group ( P  < 0.05). Oxygen saturation were lower in the conventional ISB group and C5 ISB group than in the control group ( P  = 0.01). Overall patient satisfaction scores were higher in the C5 ISB group than in the control or conventional ISB group ( P  < 0.01). Conclusion: The C5 approach for ISB provides analgesia as effectively as the conventional approach following arthroscopic shoulder surgery, with the advantages of minimal numbness and weakness.